Pulmonary artery sarcoma masquerading as a pulmonary embolism. Issue 2 (26th February 2021) - Gnanalingam, Chevanthy; Wright, Matthew; Ahmed, Yasser
Abstract : A 52-year-old woman was referred to the respiratory team with worsening shortness of breath for the last 3 months, which had deteriorated significantly over the last 2–3 weeks. She underwent a CT pulmonary angiogram, which was reported locally as showing a large pulmonary embolism. Given the chronic history and appearance of the thrombus, the patient was referred to a specialist pulmonary vascular disease multidisciplinary team and underwent a PET-CT scan with the diagnosis being felt to be more consistent with a pulmonary artery sarcoma. Within 4 weeks, she underwent a pulmonary endarterectomy which confirmed the presence of an extensive mass. She underwent bilateral endarterectomy and pulmonary artery valve replacement, with subsequent improvement of her breathlessness back to premorbid baseline. Postoperative histology has confirmed a pulmonary artery angiosarcoma. Alternate imaging modalities and early referral to a specialist unit allowed as early a diagnosis as possible with good symptomatic benefit.